EVALUASI IMPLEMENTASI PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) PADA KONSTRUKSI RUMAH TINGGAL (Studi Kasus Perumahan Kalisapu Permai) - Oktavian Ashab Alkahfi; Yulia Feriska; Moh. Tolani (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Occupational Safety and Health (OHS) is one of the programs that must be implemented in accordance with standard operating procedures (SOP) during construction development in order to protect workers from work accidents that can interfere with workers' activities. Kalisapu permai housing construction needs to be analyzed regarding K3 in order to find out how the implementation of the occupational safety and health (K3) program is adequate, the relationship of variables that can affect K3 to the implementation of the K3 program in the housing construction, and what variables are very influential in the construction. The method used is descriptive hypothesis, multiple regression analysis, multiple correlation analysis, relative contribution. The results of this test show that the implementation of the occupational safety and health (K3) program in kalisapu permai housing construction is classified as good. The relationship between variables that can affect K3 can be made in the equation Y = 5.732 + 0.05 X1 + 0.11 X2 + 0.46 X3, with variables X1 Management Policy, X2 machinery and work equipment. X3 personal protective equipment shows that the implementation of OHS (Y) can be influenced by these three variables. The magnitude of the variable influence obtained from the F test with a correlation value of 0.66 indicates a strong relationship with a coefficient of determination of 44.44%. While the most influential variable is personal protective equipment with a value of 60.02% obtained from the calculation of relative contribution.